Fake News e o movimento organizacional de enfrentamento - Silva, Michelle Cristina Taborda da (2022)
In a democratic environment, the free circulation of information, ideas and opinions is, in theory, guaranteed. However, if they start from a non-factual object, it can be said that there is a compromising noise in the communication that will probably result in untrue, false or fake information. Thus, this study will address the phenomenon of fake news and the role of organizations that face them. Its general objective is to analyze how some organizations act in the confrontation of fake news nowadays. Even more specifically, it aims to identify which actions to combat fake news the organizations studied apply in the electoral and political sphere. The present research is justified by looking at non-factual information and realizing that it has advanced in recent years, through technology, and resulted in relevant behavioral and social changes, even capable of influencing political, ideological and sanitary scenarios of the entire world population. To implement a qualitative research, it was adopted the semi-structured interview data collection method with a realistic approach that was submitted to thematic content analysis, with an exploratory descriptive purpose for this discussion. The interviews were carried out with some of the few organizations that work directly on combating the inventiveness of rumors in the politicalelectoral context, such as: Sleeping Giant Brasil, Comprova Fact Checking Project, United Nations (UN) and Tribunal Superior Eleitoral (TSE). Finally, not in order to idealize a court of truth, but just to observe Organizations and measures capable of helping society to not trivialize the measurement criteria, and to avoid behavioral differences with relevant social reflexes, it was sought to achieve the goals listed and answer the research question: what are the difficulties that organizations face in combating fake news. The conclusion obtained is that the human behavioral factor of spectacularization, the lack of education to use the medias and social communication and the spokespersons of great influence in the country are the main difficulties faced by Organizations, followed by the financial interests that permeate the public and private relationship, especially with regard to social media companies.